Genre modifications of historical and biographical fiction about W. Shakespeare in 21st century Anglophone literatures - Aliakseyenka, Yanina A. (Journal of the Belarusian State University. Philology, 2025)
The article deals with the specifics of historical and biographical fiction about W. Shakespeare in 21st century Anglophone literatures. The reasons for the classic’s mythologisation in the historical perspective and the universal features of his image reception in various national literatures (American, Australian, Canadian, English, Irish, Scottish) are distinguished on the example of chosen texts. The modifications of the novels about the bard and their genre-forming features are identified. The relevance of the topic and the theoretical significance of the results are due to the need to systematise the forms of documentary fiction and to determine the most frequent precedent texts in order to develop strategies for the adequate translation of novels about the playwright.
Keywords: Anglophone literatures; biographical myth; genre syncretism; intertextuality; historical and biographical discourse; reception; fact and fiction